Thermoluminescent properties of HfO2:Ti after exposure to X-rays. (July 2016) - Fiaczyk, Karolina; Wojtowicz, Andrzej J.; Drozdowski, Winicjusz; Brylew, Kamil; Zych, Eugeniusz
Abstract: Radio- and thermoluminescent properties of HfO2 :Ti sintered ceramics were investigated in the temperature range of 10–300 K. Fabrication atmosphere altered somewhat the efficiency of radioluminescence but did not affect the spectral distribution of the broad scintillation band covering the 380–570 nm range of wavelengths and peaking at 522 nm at 10 K and about 490 nm at 300 K. The analogous shift was seen in photoluminescence. Scintillation efficiency was continuously growing from 10 K to 300 K, while photoluminescence intensity was stable in the 10–250 K range of temperatures and was reduced by about 30% at 300 K. Analysis of these observations allowed to conclude that diffusion of carriers generated upon the impact of high-energy photons towards the Ti emitting center is strongly temperature-dependent and inferior at lower temperatures. Upon exposure to X-rays at 10 K the ceramics stored more than 50% of the absorbed energy. This energy could be recovered later upon thermal stimulation of the ceramics. Four main thermoluminescent peaks were then produced at 95, 140, 243 and 278 K. This effect was tentatively associated with theoretically predicted self-trapping of holes in HfO2 . The so-called partial cleaning and Tmax –Tstop experiments indicated that some fraction of traps shows a continuous distribution of their depths. Highlights: Radio- and thermoluminescence of HfO2 :Ti ceramics within 10–300 K was analyzed. Energy trapping ability was proved to be independent on the fabrication atmosphere. Parameters of six traps in HfO2 :Ti ceramics were calculated.